(untitled) (AYUSHDHARA, 2019)
Childhood Obesity (Sthaulya) is one of the major non communicable diseases of the modern era, increasing in prevalence. Diet (Ahara) and life-style (Vihara) play signiﬁcant role both in the development and control of obesity Sthaulya (obesity). As per Ayurveda texts, over consumption of energy dense foods along with sedentary lifestyle hampers the functioning of Medodhatvagni results in decrease fat metabolism hence causes obesity. So Triphalaguduchyadi Vati was chosen to break the etiopathogenesis of Sthaulya and to enhance the fat metabolism. A 16 year old, 11th standard, Hindu male child visited with parents to KB OPD, IPGTRA, Gujarat Ayurved University, Jamnagar, having chief complaint of progressive weight gain since 6-7 years. Triphalaguduchyadi Vati was intervened in appropriate dose for 8 weeks along with modified diet and lifestyle. Physical and laboratory assessments were done before and after the intervention. After 8 weeks of drug intervention, there was marked relief in symptoms, also there was significant decrease in physical and laboratory parameters. After reviewing, this case study it can be concluded that Triphalaguduchyadi Vati with modified diet and lifestyle is effective treatment regimen for Sthaulya in children.